Administrative justice: the role of judiciary in administrative decisions in Malaysia / Amran Ahmad - Ahmad, Amran (Faculty of Law, 1986)
Since independent administrative law, has shown a tremendous growth in Malaysia. With an excpetion, the courts have also made a number of pronouncement bearing on administrative law. And in number of these cases, courts have shown signs of creativity, just as other courts in. other countries have done. As the states come to play an active role in regulating the citizens affairs, and as the administrative impignes on individual interest - the effect is that more cases with various aspects and problems of Administrative law subsist. Thus it is the aim of this project paper to show the role of judiciary in playing meaningful part in developing the elements of administrative behaviour towards the citizens. The courts must ensure that in so doing the administrative restrict themselves to the law, constitutionalism, democratic value and administrative exigencies. Briefly this project paper endeavoursto portray the Judiciary Role in administrative law in Malaysia. This paper seeks to highlight court pronouncements and extract principle and the court attitude therefrom. Apart from the above elements the independence of judiciary is also emphasised, to show the